IMMU-33. TARGETED IMMUNE CHECKPOINT INHIBITORS FOR INTRATUMORAL DELIVERY IN GBM. (5th November 2018) - Sanders, Stephanie; Herpai, Denise; Debinski, Waldemar
Abstract: T cells infiltrate most of solid tumors, however, in glioblastoma (GBM) the presence of these cells is heterogeneous. Using CD3 staining, we find areas of GBM tumors with very few, if any, of these immune cells or few areas that have their dense presence. Immune checkpoint inhibitors (ICI) have yet to produce clinically meaningful responses in patients with GBM. The lack of responses may be related to the limited overall presence of T cells in GBM or inefficient intratumoral trafficking of peripherally ICI-activated cells. In our strategy to make ICI more specific and more accessible to GBM tumors we redirect them to GBM tumor cells to deliver them loco-regionally. IL-13.E13K is a high affinity mutant of interleukin 13 (IL-13), preserving the binding to the cytokine's receptor alpha 2 (IL-13R2A), which is highly over-expressed on GBM cells. We have constructed two recombinant antibodies. The first consists of a single chain Fv (scFv) region of anti-CTLA-4 antibody, combined with an Fc region of human IgG1 and with IL-13.E13K (termed αCTLA4-Fc-IL-13.E13K). The second consists of the same components but with anti-PD-1 scFv instead of the αCTLA-4 (termed αPD1-Fc-IL13.E13K). Both fusion protein ICIs demonstrated competition for the IL-13R2A. In addition, the redirected immune checkpoint inhibitor αCTLA4-Fc-IL13.E13K demonstrated similar binding to CTLA-4 as did αCTLA4 antibody with Kd values in the low nM range. The αPD1-Fc-IL13.E13K, also demonstrated similar binding affinity to PD-1 as did αPD1 antibodies with Kd values also in the low nM range. Thus, αCTLA4-Fc-IL13.E13K and αPD1-Fc-IL13.E13K redirected to tumor ICI have a strong affinity for the IL-13R2A while continuing to demonstrate strong affinities for CTLA-4 and PD-1. These constructs in conjunction with other immune system stimulations like cytotoxic therapies have the potential to be effective in facilitating the interaction between T cells and GBM tumor cells directly in a tumor microenvironment.